The metamorphosis of the spectator and the spectacular competence - Helbo, André (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The article is based on the historical paradox of the spectator of a performance. Without a spectator, there is no performance, but the spectator has remained passive for a long time, he has been approached as a prisoner of his gaze, assigned to his place, excluded from the enunciative process. A profound renewal of contemporary writing has metamorphosed the role of the spectator, who has been confronted with an experience of the spectacular relationship whose principle is its very interruption. New questions arise for both the critic and the creator. To understand them, it is important to have a clear view of the different meanings of the notion of spectator. The spectator is both an individual and a member of a group: audience. These two entities have specific memories and regimes of affect. The activity of this empirical spectator can be described in terms of percepts, affects, cognitions. A second distinction can be made between the empirical spectator and the spectator as a semiotic construction. The spectator is also an actant who is the condition of the performance. In this context, he develops a modal competence: the spectacular competence.